2003
DOI: 10.1557/proc-798-y3.5
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Surface Reconstructions of AlN(0001) Films

Abstract: The growth and surface reconstructions of AlN(0001) films were studied. For moderately Alrich surfaces, the 2×6 structure is commonly observed in reflection high energy electron diffraction. It is found that this pattern consists of 2√3×2√3-R30° and 5√3×5√3-R30°r econstructions according to scanning tunneling microscopy. Similar to the Ga-rich GaN(0001) surface, these structures are determined to contain 2−3 monolayers of excess Al terminating the surface. Based on first-principles theory the structures are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Therefore, a smooth AlN (0001) surface is polar. Both experimental and theoretical studies showed reconstruction of the Al (0001) surfaces . Our goal here is for understanding the Eu preference in the bulk or at the surfaces of AlN.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a smooth AlN (0001) surface is polar. Both experimental and theoretical studies showed reconstruction of the Al (0001) surfaces . Our goal here is for understanding the Eu preference in the bulk or at the surfaces of AlN.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] To date, traditional research on AlGaN-MOCVD growth has been based either on a two-dimensional model [12][13][14] or the model of a small reactor. [15][16][17][18][19][20] Due to the great potential for development of AlGaN film , large-capacity reactors and that uniformity of growth rate and substrate thickness are required. In the MOCVD process, the gas flow, heat distribution, and concentration distribution in the reactor are vital to ensure an appropriate growth efficiency and thickness uniformity of the thin film.…”
Section: Introductionmentioning
confidence: 99%
“…(a) RHEED pattern shows 1st order streaks from excess Al overlayer when viewed along[11][12][13][14][15][16][17][18][19][20] for Al-rich growth (b) RHEED pattern shows bright sharp streaks when excess Al gets consumed.The active region of the two LEDs consists of 8-periods of the GaN quantum dot/AlN barrier heterostructure as shown inFigure 2(a). The active region quantum dots were grown in the Stranski-Krastonov mode with 25 s growth time The ninjection layer for all three LEDs is a ∼225 nm Si-doped high composition AlGaN with doping density N D ∼ 5×10 19 /cm 3 .…”
mentioning
confidence: 99%